Producción literaria de poetas sanmigueleños en la construcción de identidad cultural de los jóvenes, cantón San Miguel, provincia Bolívar, periodo septiembre – diciembre 2024. - Garófalo Mora, Ana Estefania (2025)
The literary production of San Miguel poets is a central element of the cultural identity of San Miguel de Bolívar, Ecuador. Through their work, these authors reflect the experiences, traditions, and landscapes of their society and integrate the rich original and colonial heritage that characterizes the region. Their poems and stories focus on themes such as nature, history, and social struggle, allowing readers to connect with San Miguel's cultural roots and the challenges of today.